New concept in allergy: Non-allergic rats becomes allergic after induced by Porphyromonas gingivalis lipopolysaccharide - Haryono Utomo (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2013)
Background: As a theory, seemingly it is impossible that allergic diseases, including asthma, are the result of exposure to a transmissible agent. The fact that nearly all children with asthma are allergic, but only a small proportion of allergic children have asthma, at least raises the possibility that other factors are involved. Interestingly, non-allergic children become allergic after their parents came from working in allergic people for several months. Recent research revealed that periodontal pathogens are also transmissible from mother and caregivers to infants.Therefore, it is logical that non-allergic children could become allergic after exposed to periodontopathic bacteria. However, the mechanism is still unclear. Purpose: The objective of this study is to verify a new concept that non-allergic rat may become allergic after exposed to Porphyromonas gingivalis lipopolysaccharide. Methods: Randomized control series design experimental study was conducted to 24 male Wistar rats, two experimental groups and one control group. One group was subjected to intrasulcular injection of PgLPS1435/1450. Tissue examination were done for allergy biomarkers with peroxidase immunohistochemistry for leukotriene C4 (LTC4) and eosinophilic cationic protein (ECP) in bronchus tissue. Serum level examination of interleukin 4 (IL-4), and immunoglobulin E (IgE) was done with ELISA. Data were analyzes using ANOVA. Results: after four days, LTC4 and ECP expression increased significantly (p=0.001); even insignificant, IL-4 and IgE serum level also increased. Conclusion: PgLPS is able to stimulate immunocompetent cells which changed the host immune response of non-allergic rats. Therefore, it is possible that they become allergic.Latar belakang: Menurut teori, penularan penyakit alergi termasuk asma merupakan hal yang mustahil. Fakta menunjukkn bahwa hampir semua anak penderita asma mempunyai alergi, tetapi tidak semua anak alergi menderita asma, sehingga mungkin ada faktor lain ya ng terlibat. Hal yang menarik adalah timbulnya gejala alergi pada anak non-alergi setelah orang tua mereka bekerja beberapa bulan pada orang yang alergi. Penelitian mutakhir juga menemukan bahwa bakteri periodontopatogen juga dapat ditularkan ke bayi dari ibu dan pengasuhnya. Sebagai akibatnya, sangat nasuk akal bila anak non-alergi menjadi alergi setelah terpajan bakteri periodontopatogen. Tujuan: Untuk verifikasi konsep baru, yaitu bahwa tikus non-alergi dapat menjadi alergi setelah terpajan lipopolisakarida. Metode: Pada 24 tikus Wistar jantan; dua kelompok perlakuan dan satu kontrol. Satu kelompok diberikan injeksi intrasulcular dengan PgLPS1435/1450. Pemeriksaan jaringan dilakukan pada biomarker alergi menggunakan imunohistokimia peroxidase untuk leukotriene C4 (LTC4) dan eosinophilic cationic protein (ECP) dari jaringan bronkus. Pemeriksaan kadar serum pada interleukin 4 (IL-4), dan immunoglobulin E (IgE) menggunakan metode ELISA. Data dianalisis dengan ANOVA. Hasil: Setelah empat hari, LTC4 ekspresi ECP meningkat secara bermakna (p=0.001); walau tidak bermakna, kadar IL-4 and IgE serum juga meningkat. Simpulan: PgLPS dapat merangsang sel imunokompeten sehingga dapat merubah respons imun tikus non-alergi menjadi alergi.